Project completion report: Scaling up resilient agricultural practices, technologies and services in the vulnerable areas of India - Chanana, Nitya; Khatri-Chhetri, Arun; Pimpale, Anil; Joshi, Rajashree; Saini, Sakshi; Shirsath, Paresh Bhaskar; Joshi, Arun Kumar; Aggarwal, Pramod K. (CGIAR Research Program on Climate Change, Agriculture and Food Security, 2020)
USAID/ India partnered with Climate Change, Agriculture and Food Security (CCAFS), South Asia (CCAFS), for a four-year intervention (October 2016 –September 2020) to scale out climate-resilient agricultural interventions through the Climate Smart Village (CSV) approach. The focus was on a basket of synergistic options, rather than on single technology to improve cropping and livestock development in targeted areas as a means of enhancing resilience to climate variability. CCAFS provides technical leadership and overall guidance to BAIF (an NGO) which was implementing the project on the ground. The project demonstrated a portfolio of climate resilient technologies, practices and services in 75 villages of Uttar Pradesh (Mathura district), Bihar (Nalanda district) and Madhya Pradesh (Betul district). Present report, attempts to bring out the key interventions and resulting outcomes of the project as viewed from a resilience lens.